On the validity of Fenerbahce Ozdikmen et al., 2006 as replacement for Adamas Huber, 1979 (Cyprinodontiformes: Nothobranchiidae) - Sonnenberg, Rainer; van Der Zee, Jouke R. (Zootaxa, 2008)
Recently, Fenerbahce Özdikmen et al., 2006 was proposed as a replacement name for the nothobranchiid genus Adamas Huber, 1979, which was found preoccupied by Adamas Malaise, 1945 (Hymenoptera:Tenthredinidae; Özdikmen et al. 2006). Subsequently, Huber (2007) published another replacement name, Adamans Huber, 2007, for the same genus because he challenged the availability of Fenerbahce. As currently none of the new proposed replacement names is widely used in the literature except in two publications (Huber 2007, Özdikmen et al. 2006) and in the online version of Eschmeyer’s Catalog of Fishes (1998), it might be advisable to clarify this topic before confusion can arise.